2021
DOI: 10.1093/eurjpc/zwab191
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation vs. percutaneous coronary intervention for chronic coronary syndrome: impact on morbidity and mortality

Abstract: Aims Accumulating evidence questions the clinical value of percutaneous coronary intervention (PCI) for patients with chronic coronary syndrome (CCS). We therefore compare the impact of exercise-based cardiac rehabilitation (CR) vs. PCI in patients with CCS on 18-month mortality and morbidity, and evaluate the effects of combining PCI with exercise-based CR. Methods and results A retrospective cohort study was conducted in Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A retrospective cohort study that was conducted online on real-world dataset of CCS patients showed a lower risk of all-cause mortality, rehospitalization and cardiovascular morbidity 1.5 years after diagnosis among patients who underwent exercise-based cardiac rehabilitation compared to those who were referred to PCI. Moreover, the benefit of exercise-based cardiac rehabilitation persisted in several regards (all-cause mortality, rehospitalization, acute MI or stroke) with or without the addition of PCI [ 214 ]. A home-based cardiac rehabilitation program with remote monitoring for frail patients with the help of home physiotherapist and a care giver is feasible for patients with logistical problems attending center-based cardiac rehabilitation programs.…”
Section: Results - Consensus Statementsmentioning
confidence: 99%
“…A retrospective cohort study that was conducted online on real-world dataset of CCS patients showed a lower risk of all-cause mortality, rehospitalization and cardiovascular morbidity 1.5 years after diagnosis among patients who underwent exercise-based cardiac rehabilitation compared to those who were referred to PCI. Moreover, the benefit of exercise-based cardiac rehabilitation persisted in several regards (all-cause mortality, rehospitalization, acute MI or stroke) with or without the addition of PCI [ 214 ]. A home-based cardiac rehabilitation program with remote monitoring for frail patients with the help of home physiotherapist and a care giver is feasible for patients with logistical problems attending center-based cardiac rehabilitation programs.…”
Section: Results - Consensus Statementsmentioning
confidence: 99%
“…The lower participation rate among patients with AP is, at least partially, due to the weaker recommendations (IIB) to participate in CR 3. However, aggressive lifestyle modification, including regular moderate to vigorous exercise and a healthy diet, as well as mental health and risk factor management are important in the secondary prevention of AP patients and show promising results 3,28. Accordingly, future studies should investigate the independent and additive benefits of CR in patients with AP.…”
Section: Discussionmentioning
confidence: 99%
“… 191 , 192 , 193 In a recent retrospective cohort study (n = 18,383), exercise-based CR was linked to significantly lower odds of all-cause mortality (0.37; 95% CI, 0.29-0.47) and rehospitalization (0.29; 95% CI, 0.27-0.32) compared with PCI or PCI plus CR. 194 However, results were not stratified by sex.…”
Section: Cardiovascular Rehabilitation/secondary Preventionmentioning
confidence: 99%